Cognitive and psychosocial development in children with familial hypomagnesaemia - BEREKET, ABDULLAH; ARMAN, AYŞE; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (JOHN LIBBEY EUROTEXT LTD, 2011)
Aim. Familial hypomagnesaemia (FH) is a rare genetic condition. Neuromuscular and cardiovascular manifestations are well described, whereas cognitive and psychosocial development of children with FH is generally overlooked. Methods. Nine patients with FH were evaluated with psychiatric examination and psychometric tests for cognitive and psychosocial outcome. Results. Nine children (median age 10.1 yrs, range 3-16.3 yrs, 5 boys and 4 girls) with FH participated. Psychiatric symptoms were hyperactivity, irritability, sleep and speech problems and finger sucking. Common psychiatric diagnoses were Attention Deficit Hyperactivity Disorder, borderline intelligence, mild mental retardation and speech disorders. Parent-rated Child Behavior Checklist and Child Health Questionnaire mean scores were between 0.32-0.79, and 0.4-2.12, respectively; indicating the worsened psychosocial well-being besides considerable psychiatric diagnoses. Conclusions. Cognitive and psychosocial outcome in FH may influence morbidity, quality of life and social performance. Neuropsychiatric evaluation should be a routine part of management of children with FH.
Keywords: familial hypomagnesaemia; cognitive; psychosocial; outcome; MAGNESIUM HOMEOSTASIS; GITELMANS-SYNDROME; CHRONIC ILLNESS; HYPERACTIVITY; DISORDERS; SEIZURES; ADHD